The impact on general practitioners of the changing balance of care for elderly people living in institutions - Kavanagh, Shane (British Medical Journal, 1998)
Objectives: To describe utilisation of general practitioners by elderly people resident in communal establishments; to examine variations in general practitioner utilisation and estimate the likely impact of the “downsizing” of long stay provision in NHS hospitals. Design: Secondary analyses of the survey of disability among adults in communal establishments conducted by the Office of Population Censuses and Surveys in 1986, and projection to present day. Setting: Nationally representative sample of communal establishments in Great Britain. Subjects: Disabled residents aged 65 or more without mental handicap. Results: Residents with higher levels of disability, disorders of the digestive system, resident in smaller local authority homes or larger voluntary residential homes were more likely to consult a general practitioner. For those who consulted, higher levels of disability and morbidity and residence in a private nursing home or a larger private residential home were all associated with greater general practitioner utilisation. Overall, when residents’ characteristics and size of home was controlled for, residents in nursing homes had greater predicted utilisation than those in residential care homes. People who would previously have been cared for in NHS hospitals and are now cared for in nursing homes have high predicted utilisation due to their greater morbidity and disability. Conclusion: The “downsizing” of NHS provision for elderly people has increased demand on general practitioners by 160 whole time equivalents per year in Britain.